EFFECTIVENESS OF HYPNOTHERAPY IN REDUCING ANXIETY IN ADOLESCENTS - Budi Priyanto; Ellyzabeth Sukmawati; Titi Alfiani (Universitas Pahlawan Tuanku Tambusai, 2023)
Anxiety in adolescents is a common mental health problem in society related to anxiety due to physical and emotional development, academic demands, and social pressure. Anxiety if not treated properly can affect social relationships, academic performance, and mental disorders such as chronic anxiety, and depression. Hypnotherapy has been considered one of the alternative methods to deal with anxiety in teenagers. The purpose of this study was to identify the effectiveness of hypnotherapy in lowering the risk of anxiety in adolescents. This study uses the literature review literature study method by collecting data from research articles in 2019-2022 related to the topic of hypnotherapy interventions to reduce anxiety that has been published in electronic media such as ProQuest, Pubmed, Science Direct, CINAHL with adolescent research subjects. The data analysis technique used is a descriptive qualitative method. Results: The number of Randomized controlled trials (RCTs) obtained 9 articles that met the criteria with the results showing that hypnotherapy can be effective in lowering adolescent anxiety. Hypnotherapy has been shown to be effective in lowering the risk of anxiety in adolescents, but more research is needed to compare the effectiveness of hypnotherapy with other interventions in lowering the risk of anxiety in adolescents.